2020
DOI: 10.1111/zph.12786
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Campylobacter jejuni in raccoons (Procyon lotor) on swine farms and in conservation areas in southern Ontario

Abstract: Campylobacter is a leading cause of foodborne illness in humans worldwide. Sources of infection are often difficult to identify, and are, generally, poorly understood. Recent work suggests that wildlife may represent a source of Campylobacter for human infections. Using a repeated cross‐sectional study design, raccoons were trapped on five swine farms and five conservation areas in southern Ontario from 2011 to 2013. Our objectives were to: (a) assess the impact of seasonal, climatic, location, annual and racc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Some studies had less definitive results. For example, while an inverse relationship existed for Campylobacter jejuni, these results were not consistent across all years studied [38]. The study on Strongyloids sp.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Some studies had less definitive results. For example, while an inverse relationship existed for Campylobacter jejuni, these results were not consistent across all years studied [38]. The study on Strongyloids sp.…”
Section: Resultsmentioning
confidence: 69%
“…Similarly, the Campylobacter jejuni study in broiler flocks and humans found a strong positive association between temperature and Campylobacter infections, with the greatest effect observed at maximum weekly temperatures above 13°C [77]. The study, however, demonstrated an inconsistent relationship across locations and years studied, with a key limitation being the limited temporal scale of temperature data considered, and the exclusion of humidity, an important determinant of Campylobacter transmission amongst birds [38,77,78]. This inconsistent relationship also highlights varying relationships with different temperature metrics, the main reason that we could not conduct a meta analysis.…”
Section: Discussionmentioning
confidence: 95%